Performance Management in a Multinational Company with a 360-Degree Evaluation System - Wijaya, Nur Indah (Maroon Journal De Management, 2024)
This research study examines the effectiveness of a 360 degree performance evaluation system within a multinational company, an organisation where input is solicited by the workmates, superiors, subordinates and the employees themselves. In combining these complex views the tool can provide a comprehensive evaluation of skills and developmental needs. The study design is a mixed-methods research including quantitative surveys and qualitative interviews that will be used to elaborate employee perception, culture factored to the given organisational dynamics regarding feedback. The findings indicate that despite enhancing performance insight and advancing the culture of growth, the system is faced with other challenges that include the cultural sensitivity, fear of feedback, and inconsistency across regions. Additionally, issues such as culture, and interpersonal considerations determine decisively the interpretation and implementation of feedback and hence affect the engagement of the employee. The research thus highlights the need of culturally adaptive measures and constant supervision in order to maximise the efficiency of such a system in organisations across the world.